THE QUESTION OF KYRGYZ AND KAZAKHS IN THE WORKS OF ARSTANBEK BUYLASH UULU - Baurjan Omar Uulu (Vestnik Issyk-Kulʹskogo universiteta)
In this article, the author explores the socio-political issues of Kazakhs and Kyrgyz based on the works of the Kyrgyz folk poet-improviser Arstanbek Buylash uulu. The author also examines the influence of contemporary Kyrgyz rulers, such as Khan Ormon, Jantay, and Torogeldi, as well as the Kazakh biy Tezek, on Arstanbek’s improvisational activities. The article highlights Arstanbek’s special place among the poets of the Zamanist movement. The author also analyzes the reasons why, in the 1940s, due to the political circumstances of the Soviet era, Arstanbek’s works were blacklisted and banned from study and research. Additionally, the author notes the talents of poet-improvisers Buylash uulu and Suyunbai Aron uulu, who competed in improvisational contests.